Compact tide gauge of buoy and counterweight for sea level monitoring - Garbossa, Luis Hamilton Pospissil (2020)
The sea level monitoring is extremely important for a variety of actvites like sailing, urban planning, environment, tourism and aquaculture. The monitoring is accomplished with equipments named as tde gauges. This document presents the utlity model for the installaton of a tde gauge of buoy and counterweight in a compact support structure with low cost installaton.